Production of volatile fatty acids through co-digestion of sewage sludge and external organic waste: Effect of substrate proportions and long-term operation. (1st July 2020) - Owusu-Agyeman, Isaac; Plaza, Elzbieta; Cetecioglu, Zeynep
Graphical abstract: Highlights: Co-digestion of sewage sludge and organic waste for VFA production was studied. Acetic acid dominated in short-term operation in batch mode. An increasing proportion of organic waste increased valeric and caproic acid. Caproic acid dominated during long-term operation in semi-continuous mode. VFA-rich liquid achieved higher denitrification rate than acetate and methanol. Abstract: Volatile fatty acids (VFAs) are intermediates of anaerobic digestion with high value and wide range of usage. Co-digestion of sewage sludge and external organic waste (OW) for VFA production can help achieve both resource recovery and ensure sustainable and innovative waste management. In view of this, the effect of substrate proportions on VFA production from co-digestion of primary sewage sludge and OW is studied. Long-term operation in a semi-continuous reactor was performed to assess the resilience of such a system and the VFA-rich effluent was tested for its ability to be used as carbon source for denitrification. Co-digestion was initially carried out in batch reactors with OW proportion of 0%, 25%, 50%, 75%, 100% in terms of COD and scaled up in a semi-continuous reactor operation with 50% OW. In the short-term operation in the batch mode, acetic acid dominated, however, increasing OW fraction resulted in increased valeric and caproic acid production. Moreover, in the long-term semi-continuous operation, caproic acid dominated, accounting for ≈55% of VFAs. The VFA-rich effluent from the semi-continuous reactor achieved the highest denitrification rate as a carbon source when compared with acetic acid and methanol. The results demonstrate that co-fermentation can increase VFA yield and shift products from acetic acid to caproic acid in long-term operation and the VFAs can be used within wastewater treatment plants to close the loop.